Magnesium Status in Hospitalized ICCU and non ICCU Patients With Special Reference to Waterborne Magnesium - Surati, Kirti R; Divvi, Ramavataram VSS; Nilakhe, ShreeyasPrasad D; Surati, Drishty R; Srivastav, Vipul (International Journal of Clinical and Biomedical Research, 2019)
Introduction: Low serum magnesium levels in hospitalized patients including those with cardiovascular ailments have been reported by many studies. On the other hand, magnesium therapy is advocated but has not yet been conclusively proved. In our earlier study, an association between waterborne magnesium and hypomagnesaemia in healthy subjects was reported. The present study was aimed at the contribution of waterborne magnesium among filtered and non-filtered water users in hospitalized patients. Material and methods: The present study was carried out at SMIMER, Surat. Ethical committee approval was taken. On informed consent, subjects from ICCU and general ward of Medicine unit were selected. Demographic and clinical information was collected. Serum magnesium, cardiac profile and renal profile were analyzed. Patients with conditions such as kidney, liver, brain and other critical illness were excluded. The results were expressed as Mean and SD and appropriate statistical tools were applied to arrive at conclusions. Results: Among total 557 subjects including 185 healthy subjects, 93 ICCU and 279 non-ICCU patients, the incidence of hypomagnesaemia (serum Mg < 1.7 mg/dl) was 18%, 36% and 42% was observed respectively. A significant difference (p < 0.01) in serum magnesium between filtered and non-filtered water users in healthy (1.77 ±0.36 vs 2.01 ±0.48), ICCU (1.35 ±0.44 vs 1.72±0.55), and in non-ICCU patients (1.51 ±0.59 vs 1.77±0.51) was found. No significant difference was observed in other parameters. Conclusion: Significant hypomagnesaemia was observed among users of filtered water as compared to nonfiltered water users in all groups (ICCU, non-ICCU and healthy), strongly suggestive of contribution of waterborne magnesium in maintaining normal status in the population and inadequate levels may be correlated to a higher incidence of myocardial infarction as evident from the present study wherein a 42% prevalence of hypomagnesaemia in ICCU patients was found.